2003
DOI: 10.1021/ol027146i
|View full text |Cite
|
Sign up to set email alerts
|

Binding Ability and Self-Assembly Behavior of Linear Polymeric Supramolecules Formed by Modified β-Cyclodextrin

Abstract: [structure: see text] The binding ability and self-assembly behavior of molecular interpenetration by newly synthesized mono[6-O-(4-formyl-phenyl)-beta-cyclodextrin has been investigated, revealing the formation mechanism of modified cyclodextrin from solution aggregation to solid linear polymeric supramolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…; Rekharsky & Inoue, 1998), cyclodextrins also form high-order superstructures, such as polyrotaxanes (Wenz & Keller, 1994;Harada et al, 1999;Raymo & Stoddart, 1999), catenanes (Nepogodiev & Stoddart, 1998), nanotubes (Harada & Kamachi, 1994;Harada et al, 1995) and linear polymer-like (Ramos Cabrer et al, 1999;Alvarez Parrilla et al, 2002) or Cayley-tree type conglomerates (Alvarez Parrilla et al, 2000). However, although thousands of papers have been published on these cyclic oligosaccharides, the formation by cyclodextrins of interlocked chains (Raymo & Stoddart, 1999) has received much less attention (Hirotsu et al, 1982;Kamitori et al, 1987;Harata et al, 1993;Mentzafos et al, 1996;Liu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…; Rekharsky & Inoue, 1998), cyclodextrins also form high-order superstructures, such as polyrotaxanes (Wenz & Keller, 1994;Harada et al, 1999;Raymo & Stoddart, 1999), catenanes (Nepogodiev & Stoddart, 1998), nanotubes (Harada & Kamachi, 1994;Harada et al, 1995) and linear polymer-like (Ramos Cabrer et al, 1999;Alvarez Parrilla et al, 2002) or Cayley-tree type conglomerates (Alvarez Parrilla et al, 2000). However, although thousands of papers have been published on these cyclic oligosaccharides, the formation by cyclodextrins of interlocked chains (Raymo & Stoddart, 1999) has received much less attention (Hirotsu et al, 1982;Kamitori et al, 1987;Harata et al, 1993;Mentzafos et al, 1996;Liu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In order to confirm that aggregation amβCD occurs in aqueous conditions at 1.0 mM, a solution of amβCD was prepared in ultrapure water with sonication, filtered through a 0.45 µm PES membrane filter and analyzed Figure S3). 20 For a detailed description of eq. (1) see Supporting Information.…”
Section: Aryldiazonium Precursor Synthesis and Characterizationmentioning
confidence: 99%
“…Assuming a non-cooperative self-assembly process (pKn = (n-1) pK2, n  2), the dimer formation constant is estimated at pKdim = 2.83, or Kdim ≈ 680, in excellent agreement with phenyl-CD host-guest Ka values reported by Liu et al 21 Cyclodextrins displaying modifications with aromatic groups have been reported to form crystals via one of three pathways, cavity-tail self-inclusion, packed layers and one dimensional selfassembly. [20][21][22] Crystals of amβCD were grown from solutions in both D 2 O and H 2 O over 15 days at >3 mM concentration. X-ray crystallographic data analysis revealed that the compound crystallizes by aromatic tail penetration into the cyclodextrin cavity along a screw axis to form a linear head-to-tail supramolecular structure (Figure 1c).…”
Section: Aryldiazonium Precursor Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…56 In further studies it was demonstrated by 1 H-NOESY that also in solution hydrophobic linkers attached to b-cyclodextrins are incorporated into the cavity. 57 The strong hydrophobic binding of aromatic guests to cyclodextrins was used to assemble a variety of daisy chains based on this binding motif. 57,58 Furthermore Liu et al could show that orientation, alignment and helicity of the self-assembly can be controlled by tuning or exchanging the pivot heteroatom and the tether length.…”
Section: Cyclodextrin Based Daisy Chainsmentioning
confidence: 99%